2019
DOI: 10.1073/pnas.1903059116
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical association of TET loss of function with genome-wide DNA hypomethylation

Abstract: Cancer genomes are characterized by focal increases in DNA methylation, co-occurring with widespread hypomethylation. Here, we show that TET loss of function results in a similar genomic footprint. Both 5hmC in wild-type (WT) genomes and DNA hypermethylation in TET-deficient genomes are largely confined to the active euchromatic compartment, consistent with the known functions of TET proteins in DNA demethylation and the known distribution of 5hmC at transcribed genes and active enhancers. In contrast, an unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 60 publications
13
82
0
Order By: Relevance
“…Given this paradigm, one might expect ESCs to show a global methylation increase upon TET loss, as this would shift the balance in the favor of DNMT3 activity. Counterintuitively, and as previously noted in cancer cells 41 , a slight decrease was also observed in cells lacking TETs compared with matched WT (Extended Data Fig. 10d).…”
Section: Cdko-dmrs Are Conserved and Associated With Pluripotencysupporting
confidence: 84%
“…Given this paradigm, one might expect ESCs to show a global methylation increase upon TET loss, as this would shift the balance in the favor of DNMT3 activity. Counterintuitively, and as previously noted in cancer cells 41 , a slight decrease was also observed in cells lacking TETs compared with matched WT (Extended Data Fig. 10d).…”
Section: Cdko-dmrs Are Conserved and Associated With Pluripotencysupporting
confidence: 84%
“…In contrast to our findings in TET catalytic mutant ESCs, TET knockout ESCs do not appear to exhibit global hypermethylation 58 . This discrepancy might be explained by recent findings demonstrating that TET proteins influence global DNA methylation not only via their catalytic activity but also by their genomic binding 119,120 . Knockout of TET proteins results in a seemingly paradoxical loss of DNA methylation at repetitive elements like LINEs and LTRs due to a global redistribution of DNMT3A from heterochromatin to euchromatic sites previously occupied by TETs.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, in mouse ES cells, it has been shown that Tet2 knockdown results in both loss of 5hmC and 5mC at DMRs and promoters, while only few DMRs show the expected loss of 5hmC and gain of 5mC [51]. More recently, another study from the Rao lab reported that TET deficiency in diverse cell types resulted in localized increases in DNA methylation in active euchromatic regions, concurrently with unexpected losses of DNA methylation and reactivation of repeat elements [52].…”
Section: Discussionmentioning
confidence: 99%